Effect of Heat-Treatment and Shot Peening on Low Stress Abrasion Wear Behaviour of Medium Carbon Steel - Singh, Dushyant; Saxena, A C (Journal of Agricultural Engineering, 2008)
The soil working components of agricultural machinery faces serious problem of abrasive wear. The study was conducted to investigate synergic effect of heat-treatment and shot-peening on medium carbon steel with small percentage of Boron (50B50 steel). Three heat treatment cycles (annealing, inter critical annealing, quenching and tempering) were done to obtain different material property combinations. Shot peening was done at different intensities (0.17A to 0.47A) on heat-treated specimens. Low stress abrasion wear behaviour of these steel specimens was investigated by rubber wheel dry sand abrasion tester confirming to ASTM G-65 standards. The results indicated that shot peening operation decreased the wear rate of soft as well as hard surfaces and improved the wear resistance when the peening intensity was restricted to a critical value of 0.37A.